Witness protection program: The experiences of intimidation on state witnesses in South Africa - Mphaphuli Lucy Kganyago (Temida)
Intimidation of state witnesses is a serious problem that results in the inability of the courts to prosecute cases successfully, as witnesses are afraid to give testimony because they fear for their lives. The study, of which findings are presented in this paper aimed to explore the experiences of intimidation of state witnesses in the context of the Witness Protection Program in South Africa with the objective being to examine how the intimidation of witnesses affects the outcomes of the courts. Qualitative research was conducted on a sample of 30 participants, using non-probability, purposive sampling and semi-structured interviews were conducted to collect data. Participants were witnesses and staff members in the South African Witness Protection Program. The findings show that despite the important role of the Witness Protection Program, some witnesses experience intimidation during the different stages of the criminal justice system. The study recommends approaches aimed at reducing the effect of intimidation on state witnesses.